Pengaruh Akupresur terhadap Tekanan Darah pada Penderita Hipertensi di Desa Gudang Kecamatan Cikalongkulon Kabupaten Cianjur Tahun 2024: The Effect of Acupressure on Blood Pressure in Hypertension Patients in Gudang Village, Cikalongkulon District, Cianjur Regency in 2024 - Az Zahra, Sarah; Purnama, Agus; Afrina, Rina (MPI Press, 2025)
Introduction: Hypertension is a condition in which a person experiences an increase in blood pressure with systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. It can cause many other disease complications such as coronary heart disease, stroke, heart failure, kidney failure, peripheral vascular disease and retinal vascular damage that causes vision impairment. Objectives: To determine the effect of acupressure complementary therapy on reducing blood pressure in hypertensive patients in Gudang Village, Cikalongkulon District. Method: The design of this study is a quantitative research using the Quasy Experimentation method. Respondents were given acupressure interventions at the Erjian (EX-HN6), Taichong (LR-3), Shenmen (HT-7) and Neiguan (PC-6) points 1 time a day for 3 consecutive days. The respondent criteria in this study were hypertensive patients who did not consume anti-hypertensive drugs. Result: After the intervention for 3 consecutive days, the respondents showed a significant decrease in blood pressure; The mean value of systolic and diastolic blood pressure before the intervention was 148/93.7 mmHg and after the intervention was 134/85.6 mmHg. The results of the influence test gave a P-Value of <0.001. Acupressure intervention is effective in lowering blood pressure in people with hypertension. Conclution: The administration of acupressure intervention in patients with hypertension can significantly reduce blood pressure both systolic and diastolic in patients with hypertension in Gudang Village, Cikalongkulon District.